Does 3D pASP truly reflect hyperperfusion in stroke-like lesions? - Finsterer, MD, PhD, Josef; Zarrouk-Mahjoub, PhD, Sinda (Journal of Medical Biomedical and Applied Sciences, 2018)
In a recent article, Li et al. reported about the application of3D pseudocontinuous arterial spin labelling (3D pCASL) to9 patients with mitochondrial encephalopathy, lactacidosis,and stroke-like episodes (MELAS) syndrome within onemonth after onset of a stroke-like episode (SLE)1 . 3DpCASL revealed hyperperfusion during the acute andsubacute stage of a SLE in all 9 MELAS patients1 . We havethe following comments and concerns.